2019
DOI: 10.15171/jnp.2019.45
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotection and chemotherapy sensitivity impact of metformin during cisplatin therapy; an updated review

Abstract: Chemotherapy has been accepted as the most common choice for cancer treatment. However, chemotherapy-induced toxicity and chemotherapy resistance are the two challenging barriers to the treatment. Metformin is a safe, inexpensive, and the first line drug to treat type II diabetes. It has also a significant anti-tumor effect with a selective cytotoxic efficacy on cancer stem cells. It also has renoprotective efficacy. The current study contributes to incorporating metformin to chemotherapeutic agents to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…1 Research results also show the nephroprotective 5 benefits of MET and endometriosis alleviation. 6,7 © 2024 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License xylazine, and saline solution (0.9% NaCl solution) were used for the experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Research results also show the nephroprotective 5 benefits of MET and endometriosis alleviation. 6,7 © 2024 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License xylazine, and saline solution (0.9% NaCl solution) were used for the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…8 Lactic acidosis is a significant adverse impact of MET usage, which, if not handled, can lead to a number of health complications, including liver and renal impairment. 7 Various studies have found that antioxidants can protect against organ damage from oxidative stress. 9 Black rice bran (BRB) contains anthocyanin-type cyanidin-3-glucosidase (C3G) 10 and has been proven to prevent kidney dysfunction and fibrosis, 11 protecting against kidney damage.…”
mentioning
confidence: 99%